PENGARUH PEMBERIAN EKSTRAK AIR KULIT SEMANGKA (Citrullus vulgaris Schard) TERHADAP KADAR GLUKOSA TIKUS PUTIH ( Rattus norvegicus ) YANG DIINDUKSI STREPTOZOTOSIN - Sugiyanta, Sugiyanta; As’ari, Hasyim (LPPM Universitas PGRI Adi Buana Surabaya, 2013)
Watermelon rind water extract contain of citrulline. Citrulline is a precursor of generating Nitric Oxide (NO). NO possibly reduced the level of blood glucose in reptozotosin-induced diabetic rats. This study was a laboratory experimental study completely randomized design. A number of 30 male albino Wistar rats weighting 100-200 gr were devided into six groups (N=5), with group 1 served as normal control group. The other groups were given streptozotosin to induced diabetes mellitus. The rats in control diabetic group were given CMC 0,5%, the others were given watermelon rind extracs for 8 days with different doses for each group. The results showed that serum glucose levels in posttest control group was significantly different, from that group of the watermelon rind extract 250 mg/kg bw/day (p = 0,000), groups of watermelon rind extract 500 mg/kgbw/day (p = 0,000) and groups of watermelon rind extract 1000 mg/kgbw/day (p = 0,000). The level of triglyceride in postest control was significantly different from that group of the watermelon rind extract 250 mg/kg bw/day (p = 0,000), groups of watermelon rind extract 500 mg/kgbw/day (p = 0,000) and groups of watermelon rind extract 1000 mg/kgbw/day (p = 0,000). The conclusion, the watermelon rind water extrac can be used to reduced glucose serum level (250, 500, 1000mg/kg bw) with the optimal dose was 500 mg /kgbw/day with the optimal dose was 1000 mg /kgbw/day.